Carreira, remuneração e perspectivas das lutas docentes a partir da criação do cargo de educador infantil e da lei do piso - Francilene Macedo Rocha (2017)
This dissertation sought to apprehend and analyze the changes in the career and remuneration of teachers of the Municipal Education Network of Belo Horizonte (RMEBH) from 2003, with the creation of the Early Childhood Educator (EI) and from 2008, with the implementation of the law that regulates the professional salary basis for teacher career in Brazil (National Teachers Floor Salary Law), also known as Salary Floor Law, verifying its effects on the precariousness of the teaching profession. For the analysis of the findings some classic authors were used as theoretical reference, like Marx (1978, 1996, 1996); Marx e Engels (2008); Lênin (1917); and contemporary, as Santos (2004); Bernardo (1991, 1998, 2006); Antunes (2009), Alves (2007), among others. This investigation is part of a research called National Teachers Floor Salary Law in Minas Gerais: implications on the carrear, remuneration and teacher social representation with was developed with the support of the Minas Geraiss Research Sustaining Foundation (FAPEMIG), Edictal of Universal Demand 01/2014. The research was qualitative and it was made a bibliographical study, documentary research and field research supported by interview, as an instrument of data collection. It was realized interviews with ten teachers, the Municipal secretary of education and a Union Leader. The study evidenced that the creation of a different post for Early Childhood Education, by the Law no. 8.673/2003, with a lower remuneration than the one paid for teachers who works in the Fundamental Level of Education was a strategy implemented by Belo Horizonte Municipal Government (PBH) to expand the attendance of Early Childhood Education in the city with a low cost. The unification of careers is the main demand of the teachers of Early Childhood Education. It was found that the Career Plan does not consider teachers actual needs and the salary is lagged. In the last years, RMEBH has had an explicit business deployment, especially through the Public-Private Partnership (PPP) with school construction and management power given to the private sector. The study also showed that the National Teachers Floor Salary Law (PSPN) for the public schools systems, established in 2008, is not used as a parameter in the wage-based campaigns, although it is a reference for the claim about 1/3 of the journey to extraclass activity. It is noticed that the PSPN Law induced a reduction in the remuneration and restriction of the horizon of teachers' claim. About the extraclass activity time, it was found that PBH does not effectively comply the PSPN Law and alleges purely economic reasons. Thus, it was verified that there is a process of precariousness and proletarianization of teaching work in the RMEBH, which tends to intensify with the current austerity measures in process in the country, regressive of workers' rights.